Please stay in your grave : Forest of fear - Lee, James
STORY #1 One spooky midnight, Cassandra Chew sees mysterious lights in a cemetry. Curiosity leads to danger and a hideous skeleton possesses her soul. Who can save her? Start reading and you'll start screaming, PLEASE STAY IN YOUR GRAVE!
STORY #2 A lost tribe living in the FOREST OF FEAR turns Casey Wong's school holiday camp into a nightmare of horror.With dead bodies hanging from trees,you'll be hanging on every page!
Keywords: English Language -- Fiction; English Language -- Horror Tales